Diethylenetriaminepentaacetic acid–thiourea-modified magnetic chitosan for adsorption of hexavalent chromium from aqueous solutions. (15th November 2021) - Liu, Shejiang; Gao, Jing; Zhang, Li; Yang, Yongkui; Liu, Xiuli
Abstract: Chromium pollution is a serious environmental problem given that like most heavy metals, Cr tends to persist and accumulate in the environment. In this study, diethylenetriaminepentaacetic acid–thiourea-modified magnetic chitosan (DTCS-Fe3 O4 ) was synthesized for use as an adsorbent for Cr(VI) removal from aqueous solutions. The effects of various treatment conditions on the Cr(VI) adsorption performance of DTCS-Fe3 O4 composite as well as the kinetics were elucidated. Moreover, by observing the structure and morphology of DTCS-Fe3 O4, the possible Cr(VI) adsorption mechanism was proposed. DTCS-Fe3 O4 exhibited a maximum adsorption capacity of 321.3 ± 6.0 mg g −1 . Further, the adsorption process, which followed the Langmuir model for monolayer adsorption, was predominantly governed by chemical adsorption, and could be fitted using the pseudo-second-order kinetics model. Furthermore, given its ease of preparation, low cost, and remarkable performance, it is expected that the DTCS-Fe3 O4 composite would find wide practical application in the removal of toxic Cr(VI) from wastewater. Graphical abstract: Unlabelled Image Highlights: DTPA–thiourea-modified magnetic chitosan was synthesized for Cr removal. Cr adsorption by adsorbent follows Langmuir & pseudo-second-order kinetics models. Adsorption of Cr by adsorbent is governed by multiple mechanisms. These include electrostatic attraction, ion exchange, and reduction reactions. Adsorbent could also be regenerated readily with high desorption efficiency.